(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
A complete Jurassic succession, recording the evolution from platform margin to a deep-water basin, is exposed at Mt. Mangart in the Julian Alps. The succession is a part of the Julian Nappe, where the Southern Alps overlap with the Dinarides. In the Jurassic, the area comprised part of the south Tethyan passive continental margin. The section was studied sedimentologically in detail and dated with radiolarians. It is divided into five lithostratigraphic units: Unit 1: Lower Jurassic shallow-water peloidal and oncoidal limestones; Unit 2: Pliensbachian distal shelf limestones rich in juvenile ammonites and sponge spicules topped by an Fe-Mn hardground; Unit 3: lower to possibly middle Toarcian sequence of black shales with interbedded siliceous limestone; Unit 4: upper Bajocian/Bathonian to lower Tithonian cherts, cherty limestones, and carbonate gravity-flow deposits; Unit 5: upper Tithonian red nodular cherty limestones with abundant calpionellids and aptychi. A stratigraphic gap, comprising the late Toarcian to early Bajocian, separates Unit 4 from Unit 3. In general, the succession correlates well with known Tethyan transgressive/regressive facies cycles. In addition, two periods of accelerated subsidence were recognized, the first, in the Pliensbachian, drowned the platform, the second, prior to the late Bajocian, created accommodation space for resedimented carbonate deposits from the adjacent Friuli Carbonate Platform. The present day position of the succession is between the Belluno Basin to the west and the Slovenian Basin to the south. The hitherto described successions of these two basins were located more distally from the Friuli Carbonate Platform than the Mt. Mangart succession.